Cost mitigation of factor investing in emerging equity markets - Kay Stankov; Dirk Schiereck; Volker Flögel (Journal of Asset Management, 2024)
At the beginning of factor investing research, the investment universe concentrated on developed markets and transaction costs were paid little attention. Expensive trading costs of factor investing in emerging equity markets influence optimal portfolio decisions. Based on a total costs estimate of factor-based portfolio tilts, a simple cost-mitigation approach increases net performance. Exploiting the structure of market impact, we indirectly control the costs by limiting order sizes relative to their underlying stocks' short-term liquidity. This cost-efficient strategy yields better implementability and lower-priced turnover while a possible negative effect on gross performance is more than offset.
Keywords: G11; G12; G15; 330; Investments; Asset pricing; Trading costs; Market impact; Portfolio construction; Cost-efficiency